From Patient Care to Social Well-Being: Bridging Nursing, Optometry, Psychology, and Sociology - Aisha abduallah alqarnnas; Arwa Yahya Zakri; Wafa Ibrahim Ahmed Manai; Dhuwayhi Duhaim Abdurhman AlSuhaymi; ‏Khalid Hamad Alahmadi; Bader Salem Alamri; Enas Jamiel Almehmadi; Najla Hussain Albeladi; Hassan Hamed Albadrani; Mesferah Saad Alwadei; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Healthcare has transitioned from the biomedical model of alleviating the physical ailment of the patient to the biomedical-psycho-social model of catering to the wellbeing of the patient from the physical wellness aspect, mental wellness aspect, and the social aspect. Nursing, optometry, psychology, and sociology: striving for an interdisciplinary approach that enables the patient-centric model for each patient that takes into account their individual needs and societal impact to attain a sustainable and healthy outlook on life. Aim of work: To examine the contributions and intersections of Bridging Nursing, Optometry, Psychology, and Sociology, exploring how they collectively bridge the gap between patient care and social well-being. Methods: We conducted a comprehensive search in the MEDLINE database’s electronic literature using the following search terms: Patient Care, Social Well-Being, Nursing, Optometry, Psychology, and Sociology. The search was restricted to publications from 2016to 2024 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2024. The study was structured into various sections with specific headings in the discussion section. Conclusion:The roles of nursing, Optometry, Psychology and sociology in the health care delivery is a shift toward the holistic concepts in health care delivery where social aspects and health are looked at in parallel. This reduces the effectiveness of a single fixed approach to solve patient’s issues since this model enables the healthcare providers to treat the multifactors this not only enhances the wellbeing of the patient, but also resilience. Nursing practices on care, optometry has an interactional part, psychology is involved with mental and sociologists take interest on social factors. Such integration is crucial to respond to the pluralism of patients and the subsequent shift from contemporary medicine that lacks humanity to a life-centric model of health.